Analisis Swot dalam Menentukkan Strategi Pemasaran untuk Meningkatkan Volume Penjualan Kedai Kubo Kopi dalam Perspektif Bisnis Islam (Studi pada Kedai Kubo Kopi di Bandar Lampung) - Beatricca Shinta Azzahra; Fatih Fuadi; Liya Ermawati (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
This study aims to analyze the internal and external conditions of Kedai Kubo Kopi in Bandar Lampung using the SWOT approach and identify priority factors in marketing strategies to increase sales volume. A qualitative approach was used through interviews with owners, employees, and customers to obtain relevant data. The results of the SWOT analysis show that Kedai Kubo has strengths in high-quality manual brew coffee products, affordable prices, strategic location, friendly service, and attractive interior design. Its weaknesses include limited product variety, low profit margins, limited space during peak hours, dependence on digital promotions, and inadequate staff. Opportunities that can be utilized are the increasing public interest in quality coffee, potential collaboration with influencers, the growth of the coffee market in Indonesia, and the use of social media. The threats faced are competition from large coffee shops and franchises, fluctuations in raw material prices, changes in coffee consumption trends, and reputation risks due to inappropriate promotions. These findings indicate that Kedai Kubo Kopi needs to maximize existing strengths and opportunities, as well as overcome weaknesses and mitigate threats to increase sales volume effectively.